Estudio de factibilidad para la creación de una empresa asociativa de producción y comercialización de tomate riñón bajo invernadero de los pequeños agricultores de la Parroquia de Ascázubi, Cantón Cayambe, Provincia de Pichincha - Barahona Quelal, Adela Yomaira (2015)
The purpose of this project is analyze the feasibility of create an associative of production and marketing enterprise of tomatoes which grow in to greenhouse by smallholder of Ascazubi’s parish. The socioeconomic objective is develop the productive and marking activity of sector, while they exploit their own parish resources, which generate employment and satisfying one part of demand of the area of Cayambe parish. For the marketing research we make an investigation by quiz for the final consumers, proving that the demand of urban area of Cayambe parish are 854,554 pounds, the total offer were conformed by: Ascázubi 288.319 pounds ( applied the quiz to 6 farmers), the rest of the Pichincha province 503.681 pounds and for the Imbabura province were 8,124,600 pounds, and that showing that the project don’t have unmet demand. This project were locate at Ascázubi Parish, Cayambe canton of Pichincha province, occupying a total area of 4,000 m2 (5 grounds of the partners), in which will implement the productive process, projecting to seed 14000 tomatoes plants in the first cycle of production (6 months) and the same side with 14000 tomatoes plants in the second cycle of production.